FAKTOR-FAKTOR YANG MEMPENGARUHI PERUSAHAAN BERPINDAH KANTOR AKUNTAN PUBLIK (Studi Pada Perusahaan Manufaktur Yang Listing Di BEI TAHUN 2010-2012) - Syarifah Dalila Rahmani Djamalilleil; Ria Nelly Sari; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research is aims to get empirical evidence about the effect of audit opinion, ROA changes, financial distress, firm size, management of change, and accounting firm size on auditor switching. Population of this study is manufacturing companies listed in BEI on 2010-2012. The purposive sampling method was used to determine the sample. The data of 25 firms were then analyzed to test the hypoteses by using statistical product services solution (spss) version 17. The results of this study indicated that audit opinion, financial distress, and management of change have effect on audit switching while the other variable haven’t effect on auditor switching.Keywords: Auditor Switching, Audit Opinion, ROA changes, Financial Distress, Firm Size, Management of change, And Accounting Firm Size.